The retirement security of employee owners in ESOPs in S Corporations. Issue 3 (9th December 2019) - Wiefek, Nancy; Nicholson, Nathan
Abstract : Purpose: American workers at nearly every level of the income spectrum are not and often cannot to save properly to be secure in retirement. Addressing this challenge will require a comprehensive policy discussion by both federal and state policymakers. Employee stock ownership plans (ESOPs) are the primary form of employee ownership, and for reasons explored in this report, companies organized as S corporations are especially likely to be fully ESOP-owned. The purpose of the paper is to explore the role played by employee ownership in retirement security overall and across wage and age groups. Design/methodology/approach: The findings described in this report are derived from a survey of privately held S corporation ESOPs. The report compares these findings to nationally representative survey data. The online survey, conducted between January and March 2018, received responses from 39 companies that supplied the median and average account balances of a total of 61, 020 plan participants. It breaks new ground by presenting retirement account balances by wage and age categories (e.g. 20, 000 lower-wage workers and 8, 000 employees nearing retirement). Findings: ESOP participants represented in this survey have more than twice the average total retirement balance of Americans nationally: 170, 326 vs 80, 339. This is not just a function of higher wage ESOP employees driving the average up. ESOP employees making less than 25, 000 a year also have on average more than double the retirement savings (55, 526) compared to similar workers nationally (22, 447). Nearly all of the respondent companies (97 percent) offer at least one other retirement plan in addition to the ESOP. By contrast, 32 percent of all workers in the US workforce as a whole do not have access to any retirement benefits at work, and 49 percent of all workers are not participating in the plan that is available to them. Additionally, these S corporation ESOP companies provide an array of benefits at levels solidly higher than firms overall where comparison data exist. Certainly, these benefits make their own contribution to retirement security because workers are less likely to have to dip into savings for critical investments or expenses, such as tuition, to advance their career or unexpected medical expenses. Among the surveyed S ESOPs, workers nearing retirement have on average a median account balance of 147, 522 in their ESOP plus 98, 974 in a non-ESOP plan(s). By contrast, more than one-third (35 percent) of all workers nearing retirement have neither retirement savings nor a defined benefit pension. This percentage rises to 50 percent among low-income workers in this age bracket. As such, national data place the median account balance of all US workers aged 55–64 years at zero. Even among workers who have retirement accounts, the median balance nationally is 100, 000. A typical millennial worker (25–34 years old) at a surveyed S ESOP company has a median ESOP account balance of 22, 588 and a median balance of 11, 239 in a non-ESOP account. In contrast, the median savings of US millennials is zero. Among the surveyed S ESOPs, lower-wage employees (10.00–12.85 per hour) typically have median account balances in their ESOP of 4, 381 and in a non- ESOP plan of 2, 149. In contrast, nationally, 56 percent of workers in this category do not have access to any retirement benefits at work. This translates into a median savings for this group of zero. Finally, ESOPs are clearly associated with reduced turnover. Respondent companies report quit and separation rates that are more than two times lower than national rates. Originality/value: This is the first such study of its kind.